DNTP deficiency induced by HU via inhibiting ribonucleotide reductase affects neural tube development. (3rd February 2015) - Guan, Zhen; Wang, Xiuwei; Dong, Yanting; Xu, Lin; Zhu, Zhiqiang; Wang, Jianhua; Zhang, Ting; Niu, Bo
Graphical abstract: Highlights: Murine NTDs were successfully induced by means of hydroxyurea (HU). The impairment of dNTP was induced via inhibition of ribonucleotide reductase. dNTP deficiency induced by HU caused defective DNA synthesis and repair. Abnormal apoptosis and proliferation induced by HU affected neural tube development. Abstract: Exposure to environmental toxic chemicals in utero during the neural tube development period can cause developmental disorders. To evaluate the disruption of neural tube development programming, the murine neural tube defects (NTDs) model was induced by interrupting folate metabolism using methotrexate in our previous study. The present study aimed to examine the effects of dNTP deficiency induced by hydroxyurea (HU), a specific ribonucleotide reductase (RNR) inhibitor, during murine neural tube development. Pregnant C57BL/6J mice were intraperitoneally injected with various doses of HU on gestation day (GD) 7.5, and the embryos were checked on GD 11.5. RNR activity and deoxynucleoside triphosphate (dNTP) levels were measured in the optimal dose. Additionally, DNA damage was examined by comet analysis and terminal deoxynucleotidyl transferase mediated dUTP nick end-labeling (TUNEL) assay. Cellular behaviors in NTDs embryos were evaluated with phosphorylation of histone H3 (PH-3) and caspase-3 using immunohistochemistry and western blot analysis. The results showed that NTDs were observed mostly with HU treatment at an optimal dose of 225 mg/kg b/w. RNR activity was inhibited and dNTP levels were decreased in HU-treated embryos with NTDs. Additionally, increased DNA damage, decreased proliferation, and increased caspase-3 were significant in NTDs embryos compared to the controls. Results indicated that HU induced murine NTDs model by disturbing dNTP metabolism and further led to the abnormal cell balance between proliferation and apoptosis.